Obtaining Goats’ Dairy Products Enriched in Healthy Fatty Acids by Valuing Linseed or Hempseed as Dietary Ingredients - Ana Elena Cismileanu; Smaranda Mariana Toma; Mariana Ropota; Costin Petru Dragomir; Gabriela Maria Cornescu; Catalin Dragomir (Agriculture)
The study aimed to assess the effects of including linseeds or hempseeds in the diets of late lactation Murciano-Granadina dairy goats on the nutritional quality of the milk and cheese fat, expressed by the fatty acids profile and the healthy lipid indices. Thirty-six goats were randomly distributed in 3 groups of 12 animals each, according to a 3 × 3 Latin square design, and fed three different diets: group CON (control, with sunflower meal, 11.5% DM basis); group LIN, where sunflower meal was replaced by linseed; and group HMP, where sunflower meal was replaced by hempseeds. The replacement had no effects on the milk yields and the milk protein content as no significant differences were detected among groups. The significant increase of the fat content in the case of the LIN and HMP groups was accompanied by significant decreases in saturated fatty acids concentration and very significant increases in monounsaturated fatty acids. The content of n3 and n6-PUFAs (polyunsaturated fatty acids) increased, mainly due to a 4.1 times higher proportion of alpha-linolenic acid (ALA; C 18:3n-3) in LIN diet milk and a 1.3 times higher proportion of linoleic acid (LA; C 18:2n6c) in HMP diet milk. The conjugated linoleic acid (CLA; isomer c9, t11) was 1.9 times higher for the LIN diet and 5.05 times higher for the HMP diet. Feeding either linseed or hempseeds contributed to the reduction of the atherogenic and thrombogenic indices, increased the hypocholesterolemic: hypercholesterolemic ratio as well as the proportion of other desired fatty acids in the milk fat. The improved nutritional quality of milk, which has potentially far-reaching human health benefits, is maintained in cheese through the increase of the n3 and n6-PUFAs, especially for the LIN diet where the n6/n3 ratio decreased significantly, compared with the CON diet (3.62 vs. 6.88). The CLA concentration was significantly higher (p < 0.001) for the HMP cheese compared with the CON diet (1.89% vs. 0.78%). These effects highlight the opportunity of obtaining dairy products with improved nutritional quality using local feed resources.